The use of imipramine in a child with hinman's syndrome: Case report - Nida Limsuwan (2018)
Background: The Hinman's syndrome is a serious and unusual outcome of the dysfunctional elimination syndrome. The data about treatment of this syndrome is very limited. Objective: To describe an unusual treatment of the Hinman's syndrome in a child by using imipramine. Material and Method: A 7-year-old Thai boy presented with both diurnal and nocturnal enuresis and dribbling for one year. After many investigations were performed, the diagnosis of Hinman's syndrome was established. Finally, imipramine was used for the treatment. Results: The patient had a good response to the treatment by imipramine. Before the treatment was started, he had both diurnal and nocturnal enuresis almost every day. After one month of treatment, he became dry 4 to 5 days/week in daytime and 5 to 7 days/week at night. Conclusion: This report shows that imipramine may play a role in the treatment of Hinman's syndrome.